Naïve Students' Conceptual Development and Beliefs: The Need for Multiple Analyses to Determine what Contributes to Student Success in a University Introductory Physics Course - Chu, Hye-Eun; Treagust, David; Chandrasegaran, Chandra (Kluwer Academic Publishers, 2008)
This research involved naïve physics learners who were interested in majoring in science or engineering. In a semester-long quasi-experimental study, open-ended pretests and weekly interviews were used to analyse the progressive development of students’ conceptions relating to sound and wave motion. Semi-structured interviews were also conducted to elucidate: (1) how their conceptions developed from everyday conceptions to unclear scientific conceptions to scientific conceptions, and (2) their beliefs of physics knowledge. Despite efforts to enable these students to learn physics, the findings showed that only two out of ten students developed acceptable physics conceptions during the course that would enable them to pursue the subject to a higher level. Also, students’ conceptual development was found to be related to their cognitive understanding and to epistemological beliefs of physics. Therefore, to facilitate naïve physics learners’ success in a general physics course, in addition to the acquisition of content knowledge, explicit emphasis needs to be placed on the nature of physics knowledge.